2006
DOI: 10.1016/j.jacc.2005.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Coronary Artery Disease in Asymptomatic Patients With Type 2 Diabetes Mellitus

Abstract: An "aggressive" diagnostic approach, requiring coronary angiography in asymptomatic DM2 patients with < or =1 associated RF for CAD and abnormal MCE, identified patients with a subclinical CAD characterized by a more favorable angiographic anatomy. The criterion of > or =2 RFs did not help to identify asymptomatic patients with a higher prevalence of CAD and is only related to a more severe CAD with unfavorable coronary anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
142
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(154 citation statements)
references
References 33 publications
(19 reference statements)
6
142
2
4
Order By: Relevance
“…26) It already has been shown that the number of risk factors is not associated with the prevalence of coronary artery disease in diabetic patients, because the severity of a risk factor is not similar in each patient. 28,29) Our study again has shown no association between the number of additional risk factors and the prevalence of significant stenosis or high-risk plaque in asymptomatic diabetic patients (Figure 3). …”
Section: Validity Of Coronary Ct Angiography For Screening Testmentioning
confidence: 63%
“…26) It already has been shown that the number of risk factors is not associated with the prevalence of coronary artery disease in diabetic patients, because the severity of a risk factor is not similar in each patient. 28,29) Our study again has shown no association between the number of additional risk factors and the prevalence of significant stenosis or high-risk plaque in asymptomatic diabetic patients (Figure 3). …”
Section: Validity Of Coronary Ct Angiography For Screening Testmentioning
confidence: 63%
“…Although some studies have indicated that the diabetes-related cardiovascular risk depends on a number of risk factors in diabetes mellitus [30], another study has shown that the degree of atherosclerosis is unrelated to the number of risk factors in diabetes [31]. There are important differences in the inclusion criteria of the study that also need to be addressed.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Several studies of asymptomatic type 2 diabetic patients have specifically examined whether risk factor burden (i.e., number of risk factors) is predictive of inducible ischemia (as determined by myocardial perfusion imaging), and these have not supported the recommendation of the 1998 consensus panel for screening asymptomatic patients with two or more risk factors (12)(13)(14). At the same time, evidence has accumulated regarding newer CAD diagnostic modalities, e.g., CT angiography (15), coronary artery calcium scoring (16,17), and cardiac magnetic resonance imaging (18), that are being implemented in strategies to diagnose and stage CAD.…”
mentioning
confidence: 99%
“…The strategy of screening patients with diabetes for advanced asymptomatic CAD is motivated by the goal of identifying patients with high cardiac risk whose outcomes might be improved through more aggressive risk factor modification, medical surveillance, or revascularization of their CAD. However, clinical factors that confer risk for adverse cardiac outcomes do not always predict which patients will have abnormal screening tests (13,14), and negative screening tests in patients with diabetes do not uniformly confer a benign prognosis (20,21 (22). In middle-aged subjects with newly detected diet-controlled diabetes in the Diabetes Intervention Study, 15% had evidence of myocardial infarction by 11 years of follow-up (23).…”
mentioning
confidence: 99%